Cine de realidad aumentada: reformulación del aparato cinematográfico: estudio de caso de A Jester’s Tale - Dr. Francisco-Julián MARTÍNEZ-CANO,Dr. José-Manuel LÓPEZ-AGULLÓ PÉREZ-CABALLERO,Dda. Eva HERNÁNDEZ-MARTÍNEZ, (Fonseca, Journal of Communication, 2023)
The emergence of immersive technologies and the recording of volumetric images are giving rise to innovative augmented reality (AR) audiovisual fiction productions. In response to this reformulation of the audiovisual narrative device and with the aim of examining the technological and ideological drifts of these immersive cinematic practices, it is necessary to explore in depth the key aspects of the evolving cinematic apparatus.